AB1303 FUNCTIONAL AND PROFESSIONAL OUTCOMES IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Boussaid, Soumaya; Aissaoui, Takoua; Rekik, Sonia; Jemmali, Samia; Ajlani, Houda; Sahli, Hela; Cheour, Elhem; Euch, Mohamed El
Abstract : Background: Rheumatoid arthritis (RA) is the most common chronic inflammatory rheumatism in adults. It affects the synovial membrane, evolves by outbreaks and can lead to joint destruction. It generates a physical disability that causes an impairment of quality of life and professional activity. Objectives: To study the socio-demographic, clinical and professional characteristics of patients and to assess the impact of RA on quality of life and professional activity. Methods: We conducted a retrospective, descriptive study on patients' files, followed at the rheumatology department of LA RABTA university hospital, for RA aver a period of ten years. The target population was patients having a professional activity at the time of the discovery of the disease. We assessed disease activity by the Disease Activity Score DAS28-CRP, work impact by the "Work Productivity and Activity Impairment" questionnaire (WPAI:RA) and quality of life by the Health Assessment Questionnaire (HAQ). The data was entered into an excel table and analyzed using SPSS software version 19.0. In all statistical tests, the significance level was set at 0.05. Results: We collected 25 cases of RA. Mean age was 50.36 ± 8.28 years with a sex ratio of 1.08. The mean age of RA was 9.8 years and the mean age of onset was 40.56 ± 9.84 years. The study population occupied a manual job in 84% of cases. The average professional seniority was 21.76 ± 12.83 years. Patients reported having stopped work because of their illness in 44% of cases. The mean of DAS28-CRP was 4.32 ± 1.57, 72% of the study population had moderate to severe RA activity. The mean HAQ was 1.38 ± 0.69 with 76% of cases suffering from "moderate to severe" or "severe to very severe disability". The evaluation of the work productivity and activity impairment by the WPAI:RA questionnaire objectified an absenteeism of 30.7 ± 9.4%, a presenteeism of 46.7 ± 26.4%, a work productivity loss of 60.4 ± 33.8% and an activity impairment of 57.2 ± 25.4%. A positive and statistically significant correlation was noted between the results of WPAI and HAQ, between the results of WPAI (except absenteeism) and DAS286CRP and between HAQ and DAS28-CRP. Conclusion: RA causes a significant functional disability that affects the professional activity and quality of life of patients. Early diagnosis and treatment of this disease can slow the progression o the disease. Occupational medicine plays an important role in the early detection and maintenance of employees with RA at work. Disclosure of Interests: None declared